Politeness and Prosody: The Effect of Power, Distance, and Imposition on Pitch Contours in Spanish - Staszkiewicz, Bruno (Language and speech, 2025)
Research in the last few decades has examined the intersection between phonetics and politeness in multiple languages. While most of the studies have analyzed the role of politeness on suprasegmental features (i.e., pitch or duration), few have considered the key contextual variables of power, distance, and imposition. This study investigates the systematic effects of power, distance, and imposition on the final intonational contours of polar questions in Central Peninsular Spanish native speakers. A total of 36 native speakers from Madrid completed a contextualized reading-sentence task in which they read aloud paragraph-length contextualizing situations and the target polar questions. The situations were balanced for two levels of power (high/low), distance (high/low), and imposition (high/low). The results from the contextualized reading-sentence task showed that the low-rising final intonational contour (L*H%) was the most employed intonational contour in every context, while the remaining contours were H*H%, H*L%, L*L%. The results confirm that L*H% is the prevailing final intonational contour in Spanish polar questions while also shedding light on the variability of other intonational configurations. In addition, the study determines whether final nuclear contours are impacted by power, distance, and impositions. The findings are discussed within the framework of Politeness Theory and the work on the phonetics and pragmatics interface.